1999
DOI: 10.1042/bj3370275
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathway leading to an activation of mitogen-activated protein kinase by stimulating M3 muscarinic receptor

Abstract: The signalling pathway leading to an activation of mitogen-activated protein (MAP) kinase subtypes Erk-1 and -2 upon stimulation of muscarinic receptor with carbachol in human neuroblastoma SK-N-BE2(C) cells was investigated. Carbachol activated Erk-1/-2 by stimulating M3 muscarinic receptor, as determined by specific antagonists for individual muscarinic receptors. The activation of Erk-1/-2 by carbachol was blocked by the inhibition or down-regulation of protein kinase C (PKC). Among the multiple PKC isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Activation of the different MAPK pathways occurs simultaneously, and there is crosstalk between ERK1/2 and p38 that is mediated by various protein phosphatases [145,185]. Moreover, it has been demonstrated that PKC phosphorylates both ERK1/2 and p38 MAPK [76,86,153] providing a link between PKC and MAPK signaling. In the presence of functioning protein phosphatases, estrogens, via maintenance of protein phosphatase activity [200,201], or specific inhibitors of ERK1/2 or PKC [202] prevent glutamate death signaling.…”
Section: Mapk Pathway Involvement In Er-independent Estrogen-indumentioning
confidence: 99%
“…Activation of the different MAPK pathways occurs simultaneously, and there is crosstalk between ERK1/2 and p38 that is mediated by various protein phosphatases [145,185]. Moreover, it has been demonstrated that PKC phosphorylates both ERK1/2 and p38 MAPK [76,86,153] providing a link between PKC and MAPK signaling. In the presence of functioning protein phosphatases, estrogens, via maintenance of protein phosphatase activity [200,201], or specific inhibitors of ERK1/2 or PKC [202] prevent glutamate death signaling.…”
Section: Mapk Pathway Involvement In Er-independent Estrogen-indumentioning
confidence: 99%
“…To analyse the effects of endogenous Ras pathway activation on NADPH oxidase complex, we stimulated SK‐N‐BE cells with the cholinergic agonist carbachol. Under these conditions, the Ras/ERK1/2 pathway is activated through the stimulation of M3 muscarinic receptors that act on Ras via G q/11 /phospholipase C/protein kinase Cε pathway (Kim et al . 1999).…”
Section: Endogenous Ras Activation By Cholinergic Stimulation Of Sk‐nmentioning
confidence: 99%
“…5B), indicating a lack of involvement of PKC α in this effect. In an additional experiment, astrocytoma cells were incubated with ingenol 3,20‐dibenzoate (IDB), a specific activator of PKC ϵ, which has been shown to downregulate this PKC isozyme selectively after prolonged incubation (Kim et al, 1999). A 24‐h preincubation with IDB caused a significant dose‐dependent reduction in carbachol‐mediated MAPK activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence that M 2 muscarinic receptors can stimulate MAPK, through the G βγ subunit (Crespo et al, 1994; Lopez‐Ilasaca et al, 1997). In case of M 2 receptors, the signaling to MAPK appears to involve Ras and phosphatidylinositol 3‐kinase (PI3K) (Crespo et al, 1994; Lopez‐Ilasaca et al, 1997), while for the other subtypes, an involvement of protein kinase C (PKC) has been suggested, albeit with contrasting results (Kim et al, 1999; Budd et al, 1999; Keely et al, 1998; Haring et al, 1998).…”
Section: Introductionmentioning
confidence: 99%